BIMBINGAN KELOMPOK MELALUI TEKNIK SOSIODAMA TERHADAP PERILAKU PROSOSIAL SISWA KELAS X SMK NUSA BHAKTI BANDUNG PADA MASA PANDEMI - Muhammad Adhika Rizqiansyah Syarifien; Euis Eti Rohaeti; Williya Novianti (IKIP Siliwangi, 2023)
This study aims to determine how the implementation of group guidance services through sociodrama techniques for class X at SMK Nusa Bhakti in developing prosocial behavior. The type of research used is qualitative research. For the subject, students are selected according to the characteristics, namely students aged 15-16 years and students in class X who have less prosocial behavior. Data was collected by interviewing homeroom teachers, BK teachers, and students who had low and high prosocial behavior. The results show that students who have low prosocial behavior can understand that prosocial behavior is very important to have and apply in the surrounding environment, it can be seen from the behavior of students who previously did not have a sense of help with the surrounding environment after being given group guidance services with sociodrama techniques. the student becomes have a sense of help towards the surrounding environment. Group guidance services through sociodrama techniques can be used as a service that can assist in developing students' prosocial behavior at school.Keywords: group guidence, sociodrama, procosial behavior